Dissonance in the discourse: A consumer’s lens to national security - Thapa, Chiran Jung (Unity Journal, 2020)
This paper attempts to demonstrate the dissonance between the highlighted themes placing people at the epicenter and yet excluding the general public and their actual security needs, examines national security from a consumer’s perspective. To underscore a dissonance in the discourse on national security, the writer explores the paradigm of national security policy. Then, it illustrates the discord between the public security needs in their everyday life and the outlined threats in the national security documents. To validate the above argument, the paper offers a new avenue on the overlooked consumer identity of human beings and demonstrates the probability and impact of threats to national security by means of the qualitative data analysis.